Application of cationic polymer to dewatering of Metro Manila septage - Adriano, Melissa M. (2008)
Septage is the solid and liquid material that is pumped out from a septic tank. It is difficult to handle and treat due to its highly variable and organic characteristic. It was observed that its characteristic of being resistant to settling and dewatering can be handled by adding a cationic polymer that facilitates coagulation-flocculation. In charge neutralization, the cationic sites of polymer adhere to the negative sites of the septage to neutralize or destabilize the repulsive forces in the colloidal suspension so that the particles can bind thus, promote solid-liquid separation. Local septage from Quezon City was almost with the same characteristics as other local septage collected from FTI-Taguig and San Mateo, Rizal. Total suspended solids were noted at 29,510 ppm, 26,460 ppm and 27,930 ppm respectively and chemical oxygen demand (COD) at 26.600 ppm, 20,400 ppm and 25,200 ppm. Other parameters like pH, biochemical oxygen demand (BOD), total solids, total volatile solids, volatile suspended solids, settleable matter, total and fecal coliform gave almost same results for the three local septage collected at different locations in Metro Manila and Rizal. The laboratory simulation of the coagulation-flocculation process was conducted using jar testing. Because the applications of jar testing is broad and varies per treatment facility, a scale-up procedure for coagulation-flocculation of local septage that caters to the specific need of Kalayaan septage treatment facility was established. Four different polymers brands were used during jar tests and evaluated its response with local septage by reducing the amount of solids in it during flocculation. Percentage of total suspended solids (TSS) and turbidity reduction of raw septage against filtrate produced after treatment was recorded to evaluate also the efficiency of each polymer used in local septage treatment. The desired final TSS was taken to be <542 ppm which is the influent load limit of the adjacent sewage treatment plant. Laboratory jar test results showed that all dosing levels produced good results in terms of TSS reduction efficiency. The optimum polymer dose (milligrams polymer used per liter septage) that can give the target TSS reduction efficiency of 98.64% with 542 ppm filtrate TSS during the jar test was attained by polymer D at 94.5 ppm in 0.30% concentration. Following were polymer B at 98.27 ppm, polymer C at at 123.6 ppm and polymer A at 144.0 ppm. These same dosing level and concentration were used to verify the effect in the plant. However, the actual adjustments made were based on actual plant operation parameters. Based on observations, improved solid and liquid separation in septage was seen by adding polymer, thus, dewatering made very effective. Better cake quality however, was visually observed in different settings aside from what appeared as drier filter cake using polymere. It also gave efficiencies of 98%, 97% and 98% in TSS, BOD and COD removal, respectively, in the analysis of filtrate. These and the percent dry solid of sludge cake at 25% are acceptable values based on the septage dewatering unit's design.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman.
Keywords: Manila Water Company Incorporated. -- Kalayaan Septage Treatment Plant; Sewage sludge -- Dewatering -- Philippines -- Quezon City; Sewage sludge -- Dewatering -- Philippines -- Taguig -- Metro Manila; Sewage sludge -- Dewatering -- Philippines -- San Mateo -- Rizal Province; Polyacrylamide; Sewage -- Purification -- Flocculation